Quantifying spatial and temporal trends in the Bonney Upwelling over the past 30 years - Alex Shute; Tim Ward; Mary Young; Mark Doubell; Kay Critchell; Daniel Ierodiaconou (Continental Shelf Research, 2026)

Macroinvertebrate community changes in response to riparian revegetation activities and land cover using historical datasets - Mariah J. Sampson; Kay Critchell; John Gooderham; Ty G. Matthews; Rebecca E. Lester (Science of The Total Environment, 2026)

Prioritising investment in kelp forest restoration: A spatially explicit benefit-cost analysis in southern Australia - Paul E. Carnell; Kym Whiteoak; Mary Young; Kay Critchell; Steve Swearer; Peter I. Macreadie; Josh McIntyre; Eric A Treml (Ecosystem Services, 2025)

Seasonal synchrony between vessel arrivals and larval production may influence the likelihood of biofouling introductions - Simone L. Stevenson; Ian Davidson; Julio Botero; Kay Critchell; Cal Faubel; Kyle Hilliam; Oliver Floerl; Melissa Welsh; Eric A. Treml (Biological Invasions, 2025)
Biofouling of ships and boats is a dominant global transport pathway for marine invasive species. Many biofouling non-indigenous species (NIS) can only be entrained by vessels and subsequently ‘discharged’ during the short-lived but highly mobile larval stage. This means their introduction to new locations is reliant on vessels arriving in suitable habitat while biofouling adults on the hull are spawning. Vessel arrivals and spawning are, however, both transient events. The influence of synchrony between shipping traffic and spawning on introductions of marine NIS is not well understood. Using New Zealand as a case study, we show that seasonality of domestic vessel arrivals is much more prevalent than for international vessel arrivals. Seasonality was identified in 35 of 58 nationwide locations receiving commercial maritime traffic. Seasonal locations most commonly experienced their shipping peaks during spring and summer, while troughs were most common during winter and autumn. This seasonal pattern produces more opportunities for introductions of spring–summer spawners, while potentially limiting introductions of autumn and winter spawners around New Zealand. Our findings indicate the importance of incorporating seasonality into models and risk-assessments of vessel-mediated incursions, and the need for more empirical data on the timing of introduction and entrainment events. There may be an opportunity to optimise surveillance and vector management efforts during periods of peak synchronicity, where the likelihood of incursions is higher.

How wide, how much? A framework for quantifying the economic and ecological outcomes of altering riparian width on agricultural land - James Malcher; Kay Critchell; Ty G. Matthews; Rebecca E. Lester (Science of The Total Environment, 2023)

Legacy community science data suggest reduced beached litter in response to a container deposit scheme at a local scale - Kay Critchell; Libby Edge; Michael J. Traurig (Marine Pollution Bulletin, 2023)

Integrating larval connectivity into the marine conservation decision‐making process across spatial scales - Dominic Muenzel; Kay Critchell; Courtney Cox; Stuart J. Campbell; Raymond Jakub; Wahid Suherfian; La Sara; Iliana Chollett; Eric A. Treml; Maria Beger (Conservation Biology, 2023)
Larval dispersal connectivity is typically integrated into spatial conservation decisions at regional or national scales, but implementing agencies struggle with translating these methods to local scales. We used larval dispersal connectivity at regional (hundreds of kilometers) and local (tens of kilometers) scales to aid in design of networks of no‐take reserves in Southeast Sulawesi, Indonesia. We used Marxan with Connectivity informed by biophysical larval dispersal models and remotely sensed coral reef habitat data to design marine reserve networks for 4 commercially important reef species across the region. We complemented regional spatial prioritization with decision trees that combined network‐based connectivity metrics and habitat quality to design reserve boundaries locally. Decision trees were used in consensus‐based workshops with stakeholders to qualitatively assess site desirability, and Marxan was used to identify areas for subsequent network expansion. Priority areas for protection and expected benefits differed among species, with little overlap in reserve network solutions. Because reef quality varied considerably across reefs, we suggest reef degradation must inform the interpretation of larval dispersal patterns and the conservation benefits achievable from protecting reefs. Our methods can be readily applied by conservation practitioners, in this region and elsewhere, to integrate connectivity data across multiple spatial scales.

Improving certainty in marine ecosystems: A biophysical modelling approach in the remote, data-limited Gulf of Carpentaria - Ruth G. Patterson; Eric Wolanski; Rachel Groom; Kay Critchell; Luke Playford; Mark Grubert; Rod Kennett; Heidi Tait; Vinay Udyawer; Jonathan Lambrechts; Hamish A. Campbell (Estuarine, Coastal and Shelf Science, 2023)

Comparing spatial conservation prioritization methods with site‐ versus spatial dependency‐based connectivity - Dominic Muenzel; Kay Critchell; Courtney Cox; Stuart J. Campbell; Raymond Jakub; Iliana Chollett; Nils Krueck; Daniel Holstein; Eric A. Treml; Maria Beger (Conservation Biology, 2023)
Larval dispersal is an important component of marine reserve networks. Two conceptually different approaches to incorporate dispersal connectivity into spatial planning of these networks exist, and it is an open question as to when either is most appropriate. Candidate reserve sites can be selected individually based on local properties of connectivity or on a spatial dependency‐based approach of selecting clusters of strongly connected habitat patches. The first acts on individual sites, whereas the second acts on linked pairs of sites. We used a combination of larval dispersal simulations representing different seascapes and case studies of biophysical larval dispersal models in the Coral Triangle region and the province of Southeast Sulawesi, Indonesia, to compare the performance of these 2 methods in the spatial planning software Marxan. We explored the reserve design performance implications of different dispersal distances and patterns based on the equilibrium settlement of larvae in protected and unprotected areas. We further assessed different assumptions about metapopulation contributions from unprotected areas, including the case of 100% depletion and more moderate scenarios. The spatial dependency method was suitable when dispersal was limited, a high proportion of the area of interest was substantially degraded, or the target amount of habitat protected was low. Conversely, when subpopulations were well connected, the 100% depletion was relaxed, or more habitat was protected, protecting individual sites with high scores in metrics of connectivity was a better strategy. Spatial dependency methods generally produced more spatially clustered solutions with more benefits inside than outside reserves compared with site‐based methods. Therefore, spatial dependency methods potentially provide better results for ecological persistence objectives over enhancing fisheries objectives, and vice versa. Different spatial prioritization methods of using connectivity are appropriate for different contexts, depending on dispersal characteristics, unprotected area contributions, habitat protection targets, and specific management objectives. Comparación entre los métodos de priorización de la conservación espacial con sitio y la conectividad espacial basada en la dependencia

Plastic Pollution and Small Juvenile Marine Turtles: A Potential Evolutionary Trap - Emily M. Duncan; Annette C. Broderick; Kay Critchell; Tamara S. Galloway; Mark Hamann; Colin J. Limpus; Penelope K. Lindeque; David Santillo; Anton D. Tucker; Scott Whiting; Erina J. Young; Brendan J. Godley (Frontiers in Marine Science, 2021)
The ingestion of plastic by marine turtles is now reported for all species. Small juvenile turtles (including post-hatchling and oceanic juveniles) are thought to be most at risk, due to feeding preferences and overlap with areas of high plastic abundance. Their remote and dispersed life stage, however, results in limited access and assessments. Here, stranded and bycaught specimens from Queensland Australia, Pacific Ocean (PO; n = 65; 1993–2019) and Western Australia, Indian Ocean (IO; n = 56; 2015–2019) provide a unique opportunity to assess the extent of plastic (> 1mm) ingestion in five species [green ( Chelonia mydas ), loggerhead ( Caretta caretta ), hawksbill ( Eretmochelys imbricata ), olive ridley ( Lepidochelys olivacea ), and flatback turtles ( Natator depressus )]. In the Pacific Ocean, high incidence of ingestion occurred in green (83%; n = 36), loggerhead (86%; n = 7), flatback (80%; n = 10) and olive ridley turtles (29%; n = 7). There was an overall lower incidence in IO; highest being in the flatback (28%; n = 18), the loggerhead (21%; n = 14) and green (9%; n = 22). No macroplastic debris ingestion was documented for hawksbill turtles in either site although sample sizes were smaller for this species (PO n = 5; IO n = 2). In the Pacific Ocean, the majority of ingested debris was made up of hard fragments (mean of all species 52%; species averages 46–97%), whereas for the Indian Ocean these were filamentous plastics (52%; 43–77%). The most abundant colour for both sites across all species was clear (PO: 36%; IO: 39%), followed by white for PO (36%) then green and blue for IO (16%; 16%). The polymers most commonly ingested by turtles in both oceans were polyethylene (PE; PO-58%; IO-39%) and polypropylene (PP; PO-20.2%; IO-23.5%). We frame the high occurrence of ingested plastic present in this marine turtle life stage as a potential evolutionary trap as they undertake their development in what are now some of the most polluted areas of the global oceans.

Environmental Drivers of Variation in Bleaching Severity of Acropora Species during an Extreme Thermal Anomaly - Mia O. Hoogenboom; Grace E. Frank; Tory J. Chase; Saskia Jurriaans; Mariana Álvarez-Noriega; Katie Peterson; Kay Critchell; Kathryn L. E. Berry; Katia J. Nicolet; Blake Ramsby; Allison S. Paley (Frontiers in Marine Science, 2017)